Hubungan Tingkat Pendidikan, Pendapatan, dan Lama Berjualan dengan Pengetahuan Mengenai Rhodamin B pada Pedagang Minuman dalam Aplikasi GoFood dan GrabFood di Wilayah Surabaya Timur - Dzakiyyatul Fikrah 'Arifah; Trias Mahmudiono (Universitas Airlangga, 2023)
Background: Food safety is one of the essential requirements for a food to be consumed. Rhodamin B is a synthetic dye that has negative health effects. Although it has a negative impact on health and has been banned from using it, there are still some findings in the community on Rhodamin B's use of food. Knowledge of additional ingredients that may and are prohibited from their use in food is important for traders as it relates to food safety that will result in consumer health. Knowledge is influenced not only by education level but also by other factors such as economic level, and experience. Objectives: To analyze the relationship between education level, seller's income, and business age toward knowledge about Rhodamin B among GoFood and GrabFood beverages seller in East Surabaya. Methods: This research was an analytical observational study with cross-sectional designs. Research was conducted in East Surabaya and Nutrition Laboratory, Faculty of Public Health, Airlangga University from March to June 2022. The study samples were taken using simple random sampling and size of the sample was searched using Slovin formula. The study consisted of 68 beverages seller with the same size in the sample of red drinks that were tested. The questionnaire consisted of beverages seller characteristic and 13 questions of knowledge that have been tested for validity and reliability. Data analysis using Spearman Rank Test was performed in this study. Results: The results of the study found that respondents mostly had a level of education at the high school level (64.7%), income less than regional minimum wage (86.8%), business age less than equal 5 years (97.1%), and low level of knowledge (47.1%). Study showed that knowledge about Rhodamin B has no significant relationship with education level (p=0.434), seller income (p=0.599), and business age (p=0.531). Conclusions: The level of education, seller's income, and business age were not related to the level of beverages seller knowledge of Rhodamin B. Therefore, subsequent studies are recommended to examine the relationship of one's knowledge with other variables such as information access, environment, and social culture over a wider and more varied region.